Prices and Pareto Optima - Sjur Flam; A. Jourani (Lund University, School of Economics and Management, Department of Economics, 2006)
We provide necessary conditions for Pareto optimum in economies where tastes or technologies may be nonconvex, nonsmooth, and affected by externalities. Firms can pursue own objectives, much like the consumers. Infinite-dimensional commodity spaces are accommodated. Public goods and material balances are accounted for as special instances of linear restrictions.
Keywords: C60; D50; D60; 330; first and second welfare theorem; weak and strong Pareto optimum; nonconvex tastes or technologies; public goods; externalities; local separation; subdifferentials; normal cones